Polska godność narodowa w świetle prawa karnego - Kulesza, Witold (Czasopismo Prawno-Historyczne, 2018)
Poland is contemporarily the only country in Europe where the law includes criminal liability for publically defaming the nation or for being disrespectful towards it. This makes the national dignity an independent legal interest. Consequently, it seems worthwhile to pay attention to the origins of the regulations which protect this particular legal interest which were introduced into the Polish law in 1932. Moreover, it creates the need for a commentary on the statutory description of the acts which break the law. It also necessitates the portrayal of the issues created on the grounds of the practical application of the sanctionative norms in the modern world. Historical roots are the reason behind the way national dignity is currently perceived and felt. Furthermore, the historical experiences determine the direction of the interpretation of the applicable law which protects the nation’s dignity. To put it in other words, the present-day interpretation of the penal norms is based on public history and as such it constitutes the historical interpretation which leads to a prescriptive understanding of the semantics of these terms. The aforementioned contemporary interpretation seeks to answer the question what type of behaviour is characterised by the perpetration of “disrespect”. Furthermore, it aims to answer which acts can be defined as a show of contempt which is equal to “defaming” the Polish nation. Consequently, the objective of the following article is to look at the contemporary law through the historically determined prism of symbolic criminalization of behaviours which attack Polish national dignity as well as to give examples of modern incriminating public statements. The provisions of criminal law which stipulate criminal liability for public defamation and disrespecting the nation have not changed since it was introduced into the Polish law. Despite this fact, the current assessment of behaviour as a violation of the nation’s dignity is influenced by the tragic 20th-century history and its memory as a legal interest. In the course of the study of the specific instances of behaviour which were not anticipated by the pre-war legislator, one needs to attempt to point to the reasons behind preserving their punishability.